Gamification Design for Waste Problems in Public Space Case Study: Gajah Tunggal Park, Tangerang - Nadia Mahatmi; RR. Mega Iranti (Jurnal Desain Komunikasi Visual Nirmana, 2019)
Waste is a problem that is always faced in every major city in Indonesia. Tangerang is one of the big cities in Indonesia that also faces problems with garbage. Even though every public space in Tangerang has provided trash bins, the level of community participation in disposing of garbage in its place is still low. To increase community participation, gamification can be used. However, before the gamification is designed, it has to first know the intrinsic motivation of people wanting to dispose of garbage in its proper place so that the gamification design is effective.